Traceable distribution of fish products: state of the art of blockchain technology applications to fish supply chains - Tokkozhina, U.; Martins, A.; Ferreira, J. (INTSYS 2022, 2022)
Fish products traceability is a sensitive issue for supply chains (SCs) involved in the capturing processes and successful distribution of these commodities. Full transparency and traceability of fish products’ locomotion has a potential to stop the flow of illegally or unethically caught/processed fish. Blockchain technology (BCT) is considered to become a crucial part of the fish traceability solution, providing an end-to-end visibility, thus creating value for all stakeholders, including final consumers. In this study, we are aiming to explore the current state of the BCT implementations to the fish distribution SCs This study applies a systematic literature review (SLR) approach of academic literature to reveal the status quo of BCT adoption in the fish and seafood SC cases, revealing the opportunities it holds in improving the levels of traceability, as well as the challenges that were identified in extant literature that need